Scale-dependent influence of multiple environmental drivers on estuarine macrobenthic crustaceans - Lam-Gordillo, Orlando; Lohrer, Andrew M.; Douglas, Emily; Hailes, Sarah; Carter, Kelly; Greenfield, Barry (Frontiers in Marine Science, 2023)
Estuarine ecosystems are transitional environments, where land, freshwater, and marine ecosystems converge. Estuaries are also hotspots of ecological functioning and considered highly economically and culturally valuable for the ecosystem services they provide to humankind. However, multiple stressors (e.g., nutrient and sediment loading, pollution, climate change) are challenging threatening the survival of estuarine organisms and therefore affecting the functions and services estuarine ecosystems provide. In this study, we investigated the influence of multiple environmental variables on long-term estuarine crustacean data across several estuaries in New Zealand. We focused on responses of specific crustacean groups and total crustacean abundance and richness to freshwater, ocean, and climate variables as drivers of change at large, medium, and fine spatial scales. Our analyses revealed that the abundance and richness of crustaceans, as well as the abundance of specific crustacean groups (i.e., Amphipoda, Decapoda, Cumacea, Tanaidacea), were influenced by unique combinations of environmental variables, resulting in scale dependent interactions. We also identified negative relationships between estuarine crustaceans and drivers, with decreased abundance and richness of crustaceans as the magnitude of drivers increased. Sea Surface Temperature (SST) and climate-related drivers (Southern Oscillation Index, SOI) were the dominant drivers of affecting estuarine crustaceans, yet sediment muddiness negatively affected crustacean communities at all spatial scales assessed. Our research suggests that the combined effects of multiple environmental drivers such as increased muddiness, ocean warming, and climate change are likely to act in a concerted way to affect the health and functioning of estuarine ecosystems. The observed interactions between macrobenthic crustaceans and climatic and oceanic drivers have important implications for understanding climate change impacts on marine ecosystems and assist management and conservation efforts.